Phonological Change in Willem Iskander Literature: Si Boeloes-Boeloes Si Roemboek- Roemboek - Royani, Ida; Najiah, Nurun (International Proceedings of Nusantara Raya, 2024)
The present study investigates a very phenomenal literature found in North Sumatera; Indonesia authored by Willem Iskander (1872). There are various phonological change occurrences which deal with its direct realization of pronunciation on the use of old Mandailing language. By using qualitative methods to analyze the literature materials in the book, this study reveals that phonological change appears in the form of assimilation, deletion, dissimilation, vowel modification (monophthongization), and insertion. The analysis also figures out that there occurs repetition on the use of the same words in the different pages and titles. The results were obtained after reading the entire book and analyzing the process of change. At the end, the researcher clarified that the occurrences of those changes were naturally realized by native speakers. Even though it was a type of written literature, the author still used oral utterances in his literacy work. Further recommendations are discussed at the end of the paper.